La prospettiva audiovisiva del Grattacielo - Rabbito, Andrea (Scenari, 2021)
The documentary by Marco Bertozzi, Cinema Grattacielo, offers itself as a metalinguistic reflection on the audiovisual language associated with the architectural figure of the skyscraper. In this way it emerges on the one hand how such a specific architectural structure has a strong impact on modern visual culture and, on the other, how its organization is recovered from the audiovisual language.